Fontolizumab, a humanised anti-interferon γ antibody, demonstrates safety and clinical activity in patients with moderate to severe Crohn's disease. Issue 8 (28th February 2006) - Hommes, D W; Mikhajlova, T L; Stoinov, S; Štimac, D; Vucelic, B; Lonovics, J; Zákuciová, M; D'Haens, G; Van Assche, G; Ba, S; Lee, S; Pearce, T
Abstract : Introduction: Interferon γ is a potent proinflammatory cytokine implicated in the inflammation of Crohn's disease (CD). We evaluated the safety and efficacy of fontolizumab, a humanised anti-interferon γ antibody, in patients with moderate to severe CD. Methods: A total of 133 patients with Crohn's disease activity index (CDAI) scores between 250 and 450, inclusive, were randomised to receive placebo or fontolizumab 4 or 10 mg/kg. Forty two patients received one dose and 91 patients received two doses on days 0 and 28. Investigators and patients were unaware of assignment. Study end points were safety, clinical response (decrease in CDAI of 100 points or more), and remission (CDAI ⩽150). Results: There was no statistically significant difference in the primary end point of the study (clinical response) between the fontolizumab and placebo groups after a single dose at day 28. However, patients receiving two doses of fontolizumab demonstrated doubling in response rate at day 56 compared with placebo: 32% (9/28) versus 69% (22/32, p = 0.02) and 67% (21/31, p = 0.03) for the placebo, and 4 and 10 mg/kg fontolizumab groups, respectively. Stratification according to elevated baseline C reactive protein levels resulted in a decreased placebo response and pronounced differences in clinical benefit. Two grade 3 adverse events were reported and were considered to be related to CD. One death (during sleep) and one serious adverse event (an elective hospitalisation) occurred, both considered unrelated. Conclusion: Treating active CD with fontolizumab was well tolerated and resulted in increased rates of clinical response and remission compared with placebo.